1997
DOI: 10.1523/jneurosci.17-11-04066.1997
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Inhibits Excitatory Transmission at Rat Hippocampal Synapses via Presynaptic Receptors

Abstract: Somatostatin is one of the major peptides in interneurons of the hippocampus. It is believed to play a role in memory formation and to reduce the susceptibility of the hippocampus to seizurelike activity. However, at the cellular level, the actions of somatostatin on hippocampal neurons are still controversial, ranging from inhibition to excitation. In the present study, we measured autaptic currents of hippocampal neurons isolated in singleneuron microcultures. Somatostatin and the analogous peptides seglitid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
121
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 62 publications
12
121
1
Order By: Relevance
“…We showed that SST reduced excitatory postsynaptic currents evoked by stimulating Schaeffer collaterals (Tallent and Siggins, 1997). This effect is likely due to presynaptic inhibition of glutamate release by SST (Boehm and Betz, 1997). Thus SST has synergistic pre-and postsynaptic actions that reduce CA1 pyramidal cell excitability.…”
Section: Sst Inhibition Of Epileptiform Activity In Hippocampal Slicesmentioning
confidence: 72%
“…We showed that SST reduced excitatory postsynaptic currents evoked by stimulating Schaeffer collaterals (Tallent and Siggins, 1997). This effect is likely due to presynaptic inhibition of glutamate release by SST (Boehm and Betz, 1997). Thus SST has synergistic pre-and postsynaptic actions that reduce CA1 pyramidal cell excitability.…”
Section: Sst Inhibition Of Epileptiform Activity In Hippocampal Slicesmentioning
confidence: 72%
“…Hippocampal neurons were prepared from neonatal rats as in Ref. 8. Glial cells were depleted by a 16-h incubation in the presence of 1 M cytarabine (AraC).…”
Section: Methodsmentioning
confidence: 99%
“…From these data, as well as a number of animal experiments on the effect of seizure activity of somatostatin, it was concluded that somatostatin has neuroprotective function and anti-epileptic action [39]. Indeed, somatostatin inhibits spontaneous and evoked epileptiform bursting in vitro [40] while reducing glutamate release in the hippocampus [41]. Somatostatin, injected intracerebroventricularly [42] or overexpressed in the hippocampus using viral tools [43] decreased the severity of seizures in vivo.…”
Section: Somatostatinmentioning
confidence: 98%